Corpus-based approach to forming communication skills in the use of idioms - Shangaraeva, Liya F.; Zakirova, Luiza R.; Deputatova, Natalya A.; Kuznetsova, Elina K. (Universidade Estadual Paulista, 2021)
The paper presents a corpus-based approach to forming communication skills which has been widely accepted nowadays. The methodological apparatus of corpus linguistics is a promising tool for language learning. The purpose of the present research is to study the potential of the Tatar National Corpus in forming communication skills in the use of Tatar idioms. Corpus-based approach has many applications in language learning from extending teaching techniques to arousing learners’ curiosity and improving communication skills. Traditionally, idioms are considered to be fixed expressions, which have a meaning that is not immediately obvious from looking at the meanings of the parts. It has become evident over the past decades that all sorts of creative modifications of idioms are quite frequent and can be varied. Most idioms are not totally opaque. Thus, they are open to the corpus-based approach. Moreover, idioms are typically based on metaphors, and metaphors as mental images are easily modifiable. The native speakers adapt them, combine them and can change parts of them. Undoubtedly, a corpus presents an opportunity to learn the authenticity of the idioms used in reality, without somebody’s selection or previous interpretation. Learning a foreign language on the basis of corpus data allows students to analyze lexical, grammatical and syntactical variations of idioms, to comprehend their semantics, and explore new variants of idioms, unrecorded in dictionaries yet.